El asentimiento informado en pediatría: Competencias de niñas, niños y adolescentes. Revisión exploratoria. - Mora-Magaña, Ignacio; Casas Martínez, Mariya de la Luz; Jiménez Gutiérrez, Carlos; Dobernig Gago, Mariana (Acta Pediatrica de Mexico)
A child is a developing human being, NOT a small adult. Just as they do not have the final height they will reach over the years, they do not have the capacity and autonomy they will achieve in adulthood, and they are persons with the dignity, rights, and principles of human beings. Informed Consent originated in the legal environment in a health-related lawsuit in 1914, while Assent was not considered until 1977. An adult's consent requires their full understanding. Informed Assent also requires that the child be competent to assent. Appelbaum and Grisso's competency approach is analyzed, as well as the results of studies that identify when a child is competent to assent. In conclusion, the advantages and challenges of Assent in research and clinical care are illustrated. In research involving children, a pediatrician and, ideally, a psychologist should always be involved. Informed consent in pediatrics should be understood as a continuous decision-making process centered on a tripartite relationship.